New Dihydroisocoumarin Root Growth Inhibitors From the Sponge-Derived Fungus Aspergillus sp. NBUF87 - Huang, Liming; Ding, Lijian; Li, Xiaohui; Wang, Ning; Cui, Wei; Wang, Xiao; Naman, C. Benjamin; Lazaro, J. Enrico H.; Yan, Xiaojun; He, Shan (Frontiers in Microbiology, 2019)
Six new dihydroisocoumarins, aspergimarins A−F (1−6), were discovered together with five known analogues (7−11) from a monoculture of the sponge-derived fungus Aspergillus sp. NBUF87. The structures of these compounds were elucidated through comprehensive spectroscopic methods, and absolute configurations were assigned after X-ray crystallography, use of the modified Mosher’s method, and comparison of electronic circular dichroism (ECD) data with literature values for previously reported analogues. Compounds 1−11 were evaluated in a variety of bioassays, and at 100 μM, both 1 and 5 showed significant inhibitory effects on the lateral root growth of Arabidopsis thaliana Columbia-0 (Col-0). Moreover, at 100 μM, 5 also possessed notable inhibition against the primary root growth of Col-0. Meanwhile, 1−11 were all found to be inactive in vitro against AChE (IC50 > 100 μM), four different types of human-derived cancer cell lines (IC50 > 50 μM), as well as methicillin-resistant Staphylococcus aureus and Escherichia coli (MIC > 50 μg/mL), and Plasmodium falciparum W2 (EC50 > 100 μg/mL), in phenotypic tests.